Answer:
f(2) = -6
Step-by-step explanation:
f(x) = 3x - 12
Let x =2
f(2) = 3*2 -12
= 6-12
= -6
Answer:
68
Step-by-step explanation:
Pythagorean theorem: a²+b²=c² a²=32² b²=60² c²=hypotenuse²
32²+60²=c²
1024+3600= c²
4624=c²
Now, take the square root of both sides of the equation to find c
=c
68=c
I hope this helps you
f(x) =sinx
f^-1(x)=arcsinx
arcsinx is inverse of sinx function
The square root of 144 is 12 hope i helped
Answer:
$10.50
Step-by-step explanation:
The formula is Balance= Principle (starting amount) x Time x Interest rate. 350 x .03 x 1 is $10.50.